1998
DOI: 10.30843/nzpp.1998.51.11672
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liquid food on fecundity and longevity of <i>Microctonus hyperodae</i> Loan

Abstract: Microctonus hyperodae Loan (Hymenoptera: Braconidae) is an introduced parasitoid of the pasture pest Argentine stem weevil, Listronotus bonariensis (Kuschel) (Coleoptera: Curculionidae). This paper describes the effect of providing honey solution to caged M. hyperodae females derived from three South American geographic populations (ecotypes) on their fecundity and longevity. Both the longevity and fecundity of parasitoids from all three ecotypes was increased when they had access to honey. There was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Adult Microctonus spp. longevity and fecundity, and therefore eficacy against pasture pests, is greatly enhanced by access to nectar (Phillips 1998). However, white clover (Trifolium repens) lowers are both too narrow and too deep to permit access to these parasitoids (Vattala et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Adult Microctonus spp. longevity and fecundity, and therefore eficacy against pasture pests, is greatly enhanced by access to nectar (Phillips 1998). However, white clover (Trifolium repens) lowers are both too narrow and too deep to permit access to these parasitoids (Vattala et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The delicate and ephemeral nature of the adult parasitoids (e.g. Phillips, 1998), coupled with their weak flight, suggest that it is less likely that the species would have actively dispersed at such a rate on its own. The dispersal rates of both M. hyperodae and M. aethiopoides are probably closely related to the flight activity of their parasitized weevil hosts.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly so after the emergence of parasitoid adults from the overwintered larval population and prior to the emergence of the first summer weevil generation. Phillips et al (1998) showed that the first summer generation of M. hyperodae adults had sufficient hosts available to lay only about 15% of its potential eggs. Presumably, such scarcity of hosts could have induced the adult parasitoid to actively disperse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endoparasitoid Microctonus hyperodae Loan (Hymenoptera: Braconidae) investigated in this study is an introduced biological control agent of Listronotus bonariensis (Kuschel) (Coleoptera: Curculionidae) (McNeill et al 2002). Previous studies have shown that the longevity of M. hyperodae adults can be signifi cantly increased by provision of either glucose or honey solutions (Hodgson et al 1993;Phillips 1998). Unfed M. hyperodae adults lived 10 days with water in the laboratory (Hodgson et al 1993;Vattala et al 2004), which was an unexpectedly long time because many other parasitoids live only 2-3 days without sugar.…”
Section: Introductionmentioning
confidence: 91%